Housing policy as a key element of urban regeneration - Olbińska, Katarzyna; Koussan, Sara (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
Urban regeneration is a complex process that aims to bring degraded areas out of a multifaceted crisis that includes social, economic, spatial, environmental and technical issues. Housing policy becomes a key component of regeneration. It includes the modernization of housing resources, activities to ensure access to the improved housing stock for people at risk of social exclusion, controlling gentrification, as well as various complementary activities aimed at social empowerment and solving the problems of the inhabitants of the regenerated areas. The aim of the article is to show the range and specifics of housing policy as part of urban regeneration and to identify the tools used, in this process including the means of social support. The study covers selected residential areas in Lodz and includes activities and initiatives carried out since the 1990s. The methods used include a literature review, desk research, and unstructured interview.